2017
DOI: 10.1177/1933719116681519
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-451a Levels Are Significantly Elevated in Women With Endometriosis and Recapitulated in Baboons (Papio anubis) With Experimentally-Induced Disease

Abstract: We have previously demonstrated that human microRNA-451a (miR-451a) endometriotic lesion expression is significantly higher compared to that of the corresponding eutopic endometrium. The objective of the current study was to examine the relationship between lesion and serum content of miR-451a and to determine the utility of serum miR-451a in distinguishing between women with and without visible signs of endometriosis. Eighty-one participants were enrolled in this study, 41 with confirmed endometriosis and 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 52 publications
4
61
0
Order By: Relevance
“…In the present study, using microarray analysis, it was found that EMS altered the expression profiles of many miRNAs. Among these aberrantly expressed miRNAs, miR-451a and miR-33b were revealed to be increased, whilst miR-20a was decreased, consistent with previous reports ( 16 , 41 , 42 ), implicating reliability of the microarray analysis performed in the present study. In previous studies, miR-202 also was found to be aberrantly expressed in endometrial tissues from patients with EMS ( 13 , 38 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, using microarray analysis, it was found that EMS altered the expression profiles of many miRNAs. Among these aberrantly expressed miRNAs, miR-451a and miR-33b were revealed to be increased, whilst miR-20a was decreased, consistent with previous reports ( 16 , 41 , 42 ), implicating reliability of the microarray analysis performed in the present study. In previous studies, miR-202 also was found to be aberrantly expressed in endometrial tissues from patients with EMS ( 13 , 38 ).…”
Section: Discussionsupporting
confidence: 92%
“…1C). Regarding miR-451a, Graham's team has recently published two studies showing increased levels of this miRNA in ovarian endometriomas that correlate with lesion size and with its serum levels (30,31). Provided that PF is mainly composed of blood components (32), and usually up-regulated proteins in serum are proportionally up-regulated in PF (33), our results are in accordance with Graham's, suggesting an important role for miR-451a as a mediator of inflammation in the peritoneal microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRs) are small, non-coding RNAs that bind to and functionally silence or degrade target mRNAs. There is a large and growing body of evidence demonstrating that miRs are involved in both the normal physiologic state and in pathologic gynecologic diseases such as endometriosis, leiomyomata and endometrial cancer ( Kuokkanen et al 2010 , Snowdon et al 2011 , Rekker et al 2013 , Marsh et al 2016 , Nothnick et al 2016 , Wilczynski et al 2016 , Chen et al 2017 a , Logan et al 2017 ). Therefore, our objectives were to identify hormonally regulated miRs in endometrial stromal cells and to investigate the effects of BPA on selected miRs.…”
Section: Introductionmentioning
confidence: 99%